Pharmacokinetics, distribution, metabolism, and excretion of body-protective compound 157, a potential drug for treating various wounds, in rats and dogs - He, Lei; Feng, Donglin; Guo, Hui; Zhou, Yueyuan; Li, Zhaozhao; Zhang, Kuo; Zhang, Wangqian; Wang, Shuning; Wang, Zhaowei; Hao, Qiang; Zhang, Cun; Gao, Yuan; et al. (Frontiers in Pharmacology, 2022)
Body-protective compound (BPC) 157 demonstrates protective effects against damage to various organs and tissues. For future clinical applications, we had previously established a solid-phase synthesis process for BPC157, verified its biological activity in different wound models, and completed preclinical safety evaluations. This study aimed to investigate the pharmacokinetics, excretion, metabolism, and distribution profiles of BPC157. After a single intravenous (IV) administration, single intramuscular (IM) administrations at three doses in successive increments along with repeated IM administrations, the elimination half-life (t1/2) of prototype BPC157 was less than 30 min, and BPC157 showed linear pharmacokinetic characteristics in rats and beagle dogs at all doses. The mean absolute bioavailability of BPC157 following IM injection was approximately 14–19% in rats and 45–51% in beagle dogs. Using [3H]-labeled BPC157 and radioactivity examination, we proved that the main excretory pathways of BPC157 involved urine and bile. [3H]BPC157 was rapidly metabolized into a variety of small peptide fragments in vivo, thus forming single amino acids that entered normal amino acid metabolism and excretion pathways. In conclusion, this study provides the first analysis of the pharmacokinetics of BPC157, which will be helpful for its translation in the clinic.